The earliest public green areas connected with Jelenia Góra, part. 2 - Jagiełło, Marzanna; Brzezowski, Wojciech (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2018)
In the third part of the 18th century the earliest public landscape gardens began to appear in the area of suburban Jelenia Góra. They were the first public parks in Silesia. When establishing them, the natural landscape features of the area were used (Karkonosze). Two of them, Hausberg and Helkon, were created at the end of the 17th century on the north-western side of the city.